Assessment Of Knowledge and Practice About Immunization Among Health Care Providers - Madhusudan Swarnkar; Vaseem N Baig; Suresh C Soni; Uma S Shukla; Javed Ali (Medsci Publications, 2016)
Introduction: Immunization is one of the most cost-effective interventions to prevent a series of major illnesses, so, it becomes important to understand the knowledge level and practices of health workers for Immunization. This study was conducted to assess awareness of health workers by their knowledge and practices of immunization. Method: This cross-sectional study was conducted on Health workers of Jhalawar (Raj) using a self-administered Questionnaire. Results: Among the 144 respondents most were ANMs (96.5%) working at sub centres. There was very good (>75%) knowledge of diseases prevented by immunization, maximum age for BCG & OPV but very poor knowledge of anaphylaxis (<25%). There was very good practice(>75%) while immunizing child with minor ailments, discarding reconstituted vaccines after 4 hours, waste handling, not revaccinating child for BCG without scar but poor practice(<50%) of not delivering  important messages. They were very poor in using counter foil for tracking of child. Increase in knowledge and practices observed with advancement of qualification but negative correlation found between previous training and length of service with both knowledge and practice of immunization. Conclusion: There is still gap in knowledge and practices of immunization among workers. Higher education of workers has impact on their knowledge and Practices.